Reinventing The Future Online Education Using Emerging Technologies - Regina Reine; Filbert H. Juwono; W. K. Wong (Tecno Scientifica Publishing, 2021)
The pandemic of Coronavirus Disease 2019 (COVID-19) has forced the teaching and learning activities to be conducted remotely. Before the pandemic, many academic institutions had offered online distance learning for selected courses. However, in practice, most of these programs were delivered as blended learning program instead of a full-fledged distance learning program. Distance learning programs faced challenges and limitations in terms of communication, integrity, and interactions compared to the traditional face-to-face teaching and learning method. Despite the challenges and limitations in distance teaching and learnings, academic staff are expected to accomplish the same (or better) outcomes than the traditional face-to-face teaching and learning. Hence, distance learning method was not popular to many academic staff and students before the pandemic time. In order to improve the quality of the full distance learning delivery, emerging technologies and more interactive platforms are being developed rapidly. This article discusses the emerging technologies and strategies to make full distance learning or remote education competitive compared to the traditional teaching and learning method. The future potential teaching and learning technology, i.e., digital twins, is also briefly presented.